2019
DOI: 10.18502/ijrm.v17i10.5484
|View full text |Cite
|
Sign up to set email alerts
|

The role of color doppler in assisted reproduction: A narrative review

Abstract: Color Doppler of perifollicular vascularity is a useful assessment tool to predict the growth potential and maturity of Graafian follicles. Power Angio is independent of the angle of insonation and morphometry and provides reliable clues to predict the implantation window of the endometrium. Color Doppler can be used for the prediction of ovarian hyperstimulation syndrome. It can also be used to identify the hyper responder and gonadotropin-resistant type of polycystic ovaries. The secretory scan of corpus lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Additionally, VEGF is one of the most relevant angiogenic factors studied to date in orchestrating folliculogenesis ( 22 ). Elevated VEGF levels in FF have been observed in both natural and IVF cycles, and it has been established that mature follicles originate from highly vascularized follicles ( 23 , 24 ). Moreover, in hormone-stimulated IVF cycles involving patients with normal ovarian response, a positive correlation was found between VEGF levels in FF and the extent of peri-follicular vascularity on the day of follicle aspiration ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, VEGF is one of the most relevant angiogenic factors studied to date in orchestrating folliculogenesis ( 22 ). Elevated VEGF levels in FF have been observed in both natural and IVF cycles, and it has been established that mature follicles originate from highly vascularized follicles ( 23 , 24 ). Moreover, in hormone-stimulated IVF cycles involving patients with normal ovarian response, a positive correlation was found between VEGF levels in FF and the extent of peri-follicular vascularity on the day of follicle aspiration ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascularity in the follicular rim first becomes visible or detectable when the follicle reaches 10 mm in diameter [ 19 ]. A mature follicle is approximately 16–18 mm in diameter, anechoic internally, and very thin-walled [ 20 ].…”
Section: Ovarian Blood Flowmentioning
confidence: 99%
“…Studies assessing the blood flow in the spiral arteries showed similar patterns of blood flow in the uterine arteries during the menstrual cycle. The RI of spiral arteries remains high in the follicular phase and decreases rapidly to a level of 0.48 3 days before ovulation [ 19 ]. On 3D Doppler, the VI, FI, and VFI increase from the midfollicular phase, peaking 3 days before ovulation, and then decrease, reaching a nadir 5 days post-ovulation, before gradually increasing again during the mid-luteal phase [ 60 ].…”
Section: Endometrial Blood Flowmentioning
confidence: 99%
“…In order to assess ovarian blood flow before to in vitro embryo development, color Doppler ultrasonography was initially used in humanassisted reproduction in the 1990s [67][68][69][70]. According to more recent studies using the pulsatility index, women with unexplained infertility exhibited reduced uterine and ovarian arterial blood perfusion during the luteal phase [71,72].…”
Section: Using Color Doppler To Assess Vascularitymentioning
confidence: 99%